ALAT PERMAINAN EDUKATIF BERBAHAN LIMBAH DALAM PEMBELAJARAN SAINS DI TAMAN KANAK-KANAK - Adiarti, Wulan (Universitas Negeri Semarang, 2009)
To teach science is basically to teach about everything in the universe. Sincetheir early age children could actually be introduced to the nature, and theirengagement in or observation of any kind of natural process may help them to enrichtheir experience and sense of science. In this sense, therefore, the use of naturalresources is important as it will also allow them to do some experiments, to furtherexplore and investigate their natural surrounding. These ability and skills areundoubtedly of a great usefulness for and in their future. Within the currentKindergarten Curriculum, science teaching is a part of the cognitive developmentenhancement. Unfortunately, in teaching science to their young learners, often,teachers adopt teaching strategies which do not suit their stage of development, forexample through the introduction of abstract scientific concept. In fact, children ofearly age think in a concrete way, and therefore, to teach them more effectively, is tosome extent to bring the subject matter to a more concrete way. This communityservice program aims to introduce the use of used objects as materials of educationaltoys, commonly used as science teaching media by the kindergarten teachers.Kata kunci : Taman kanak-kanak, Pembelajaran Sains, limbah, APE